2009
DOI: 10.1002/crat.200900460
|View full text |Cite
|
Sign up to set email alerts
|

In situ AFM investigation of 2D nucleation on the (100) face of KDP

Abstract: Surface morphology of the (100) face of potassium dihydrogen phosphate (KDP) crystals which were grown at different supersaturations at 25 °C was investigated by in situ atomic force microscopy (AFM). Various AFM images of 2D nucleation under different growth conditions were presented. It is found that the growth of KDP is controlled by polynuclear nucleation mechanism at the high supersaturation. With reduction of the supersaturation, the growth velocity of 2D nuclei becomes very slow and shows typical anisot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…However, in recent AFM experiments the growth of KDP by 2D nucleation was observed at sZ0:06 [37]. This onset supersaturation was also predicted by De Yoreo et al [13].…”
Section: Kdpmentioning
confidence: 53%
See 1 more Smart Citation
“…However, in recent AFM experiments the growth of KDP by 2D nucleation was observed at sZ0:06 [37]. This onset supersaturation was also predicted by De Yoreo et al [13].…”
Section: Kdpmentioning
confidence: 53%
“…At the supersaturation of s ¼ 0:5, for which critical nuclei were reported by Malkin et al [14] to have diameters of [35][36][37][38][39][40][41][42][43][44][45]Eq. (5) can be simplified to…”
Section: Thaumatinmentioning
confidence: 99%
“…Compared to the morphology of (100) face grown at pH value of 4.2, the height and width of macro‐steps are slightly increased when pH = 2.8 and 3.2, and the steps at those two pH values became linear (see figure b and c). However, when the pH value reaches to 2.4, a large number of 2D nuclear whose size is about 4×0.5×0.05 μm 3 appears on (100) face of KDP crystals (see figure d), whereas, it had been shown that 2D nuclear was occurred at σ > 0.06 when pH value is equal to 4.2 .…”
Section: Resultsmentioning
confidence: 99%
“…Growth parameters, such as temperature, growth direction, the purity of raw material, supersaturation and pH value are very important for crystal growth. The mechanism by which a face grows can also be dependent on the state of these parameters, specifically the supersaturation, which is frequently studied by a large number of researchers . Crystal faces grow via the spiral growth mechanism at supersaturations lower than the value where 2D nucleation and growth is the dominant mechanism, and then 2D nucleation controls crystal growth at higher supersaturation, finally it can be replaced by the rough growth mechanism when supersaturation is beyond their kinetic and thermodynamic roughening transitions .…”
Section: Introductionmentioning
confidence: 99%